Mazacon Galeas,Jasury Fernanda(2023)EVALUACIÓN DE FORMULACIONES DE GALLETAS A BASE DE HARINA DE QUINUA (Chenopodium quinoa) Y MAÍZ (Zea mays) EMPLEANDO DIFERENTES HIDROCOLOIDES.Quevedo.UTEQ.99p. - Mazacon Galeas , Jasury Fernanda (2023)
The cookie is a product that allows taking advantage of the use of different types of flour from high nutritional sources such as quinoa and corn, which provide health benefits, the cookie market is expanding, because the industry meets the changing expectations of the consumer, thus companies seek to develop cookies with high nutritional value. Due to this, the present research was developed with the objective of evaluating cookie formulations based on quinoa flour (Chenopodium quinoa) and corn (Zea mays). An AxB Completely Randomized Design was applied, with 6 treatments and 3 replications where sensory variables (odor, color, flavor, texture, general acceptability), physicochemical variables (moisture, ash, fiber, carbohydrates, protein and fat), microbiological variables (E. Coli, molds and yeasts) and economic variables (profitability and production costs). For the sensory evaluation of the cookies based on quinoa and corn flour, the non-parametric Kruskal-Wallis test was applied. It was concluded that T5 (60% corn flour - 40% quinoa flour using xanthan gum) generated a higher level of acceptance based on the sensory analysis performed. The physicochemical analysis showed optimal moisture values of less than 10%, T1 stood out in the protein parameters where there was a statistical difference, T6 stood out in the value of ash, which presents a greater amount of corn flour, but there is no significance as in the case of the parameters of fiber and fat. The microbiological analysis showed that there is an absence of the parameters analyzed, complying with cookie regulations, thus assuring the quality of the finished product. With respect to the economic analysis, a value of $0.87 was obtained for each package that includes 20 units, with a retail price of $1.14, reflecting a profitability of 30%.